2016
DOI: 10.1101/cshperspect.a022053
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Receptors for TGF-β Family Members

Abstract: Transforming growth factor b (TGF-b) family members signal via heterotetrameric complexes of type I and type II dual specificity kinase receptors. The activation and stability of the receptors are controlled by posttranslational modifications, such as phosphorylation, ubiquitylation, sumoylation, and neddylation, as well as by interaction with other proteins at the cell surface and in the cytoplasm. Activation of TGF-b receptors induces signaling via formation of Smad complexes that are translocated to the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
498
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 575 publications
(539 citation statements)
references
References 285 publications
(257 reference statements)
5
498
0
Order By: Relevance
“…HHT type 1 and type 2 result from mutations in the genes encoding endoglin, an auxiliary protein for TGFβ binding to signaling TGFβ receptors, and activin-like kinase 1, a type I receptor for TGFβ, BMP-9 and BMP-10, respectively [58]. It has been found that the majority of mutations result in the retention of these proteins in the ER [115,116].…”
Section: Tgfβ Signaling Is Controlled By Receptor Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…HHT type 1 and type 2 result from mutations in the genes encoding endoglin, an auxiliary protein for TGFβ binding to signaling TGFβ receptors, and activin-like kinase 1, a type I receptor for TGFβ, BMP-9 and BMP-10, respectively [58]. It has been found that the majority of mutations result in the retention of these proteins in the ER [115,116].…”
Section: Tgfβ Signaling Is Controlled By Receptor Traffickingmentioning
confidence: 99%
“…It has been shown that activated TGFβ receptors are internalized from plasma membrane via at least two different routes, i.e. clathrin-and caveolin-dependent endocytosis [22,58,59]. The localization of the receptor complexes in the plasma membrane microdomains, clathrin-coated pits or caveolae, predetermines the route they will follow (Fig.…”
Section: Endocytosis Of Tgfβ Receptorsmentioning
confidence: 99%
“…Seven type I receptors and five type II receptors have been identified in humans (Heldin and Moustakas 2016). Type I receptors are also known as activin receptor-like kinases (ALK-1 -b1, -b2, and -b3) are secreted in latent forms that are unable to interact with the receptors.…”
Section: Overview Of Tgf-b Signalingmentioning
confidence: 99%
“…ALK4 forms an activin receptor complex with activin type‐II receptor to transduce activin signal from the cell surface to the cytoplasm,8, 9, 10, 11 thus regulating physiological and pathological processes including embryogenesis,12 tissue homeostasis,13 wound healing,14 extracellular matrix production,15 immunosuppression, and carcinogenesis 16, 17. We recently focused on exploring the role of ALK4 in different cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%